The Prevalence of Mycoplasma Pneumoniae Among Children in Beijing Before and During the COVID-19 Pandemic - Cheng, Yuan; Cheng, Yijing; Dai, Shuzhi; Hou, Dongqing; Ge, Menglei; Zhang, Yi; Fan, Lei; Pei, Yingying; Yu, Li; Xue, Guanhua; Ma, Lijuan; Sun, Hongmei (Frontiers in Cellular and Infection Microbiology, 2022)
Objective: Mycoplasma pneumoniae (M. pneumoniae) is an important pathogen of community acquired pneumonia. With the outbreak of coronavirus disease 2019 (COVID-19), the prevalence of some infectious respiratory diseases has varied. Epidemiological features of M. pneumoniae in children from Beijing (China) before and after the COVID-19 pandemic were investigated. Methods: Between June 2016 and May 2021, a total of 569,887 children with respiratory infections from Children’s Hospital Affiliated to Capital Institute of Pediatrics (Beijing, China) were included in this study. M. pneumoniae specific-IgM antibody in serum specimens of these patients was tested by a rapid immunochromatographic assay kit. The relevant clinical data of M. pneumoniae-positive cases were also collected, and analyzed by RStudio software. Results: The results showed that 13.08% of collected samples were positive for M. pneumoniae specific-IgM antibody. The highest annual positive rate was 17.59% in 2019, followed by 12.48% in 2018, 12.31% in 2017, and 11.73% in 2016, while the rate dropped to 8.9% in 2020 and 4.95% in 2021, with significant difference. Among the six years, the positive rates in summer and winter seasons were significantly higher than those in spring and autumn seasons (p<0.001). The positive rate was the highest in school-age children (22.20%), and lowest in the infant group (8.76%, p<0.001). The positive rate in boys (11.69%) was lower than that in girls (14.80%,p<0.001). There were no significant differences in different seasons, age groups, or genders before and during the COVID-19 pandemic (p>0.05). Conclusions: Our study demonstrated that an M. pneumoniae outbreak started from the summer of 2019 in Beijing. After the COVID-19 pandemic outbreak in the end of 2019, the M. pneumoniae positive rates dropped dramatically. This may be due to the restrictive measures of the COVID-19 pandemic, which effectively controlled the transmission of M. pneumoniae. The relationships between M. pneumoniae positive rates and season, age, and gender were not statistically significant before and during the COVID-19 pandemic.